Studying brain information processing through a TicTacToe model - Suryadi (2017)
The biological brain is made up of communicating cells known as neurons, capable of emergent phenomena such as cognition and decision making. In this thesis we conduct an extensive literature review to understand a fundamental basis to these emergent phenomena - brain information processing. We then consider the Neural Engineering Framework (NEF) and build a brain model with it in the context of the TicTacToe game to further understand decision making as represented in the framework. Among other results, we found that the framework allows a natural implementation of pattern processing and that the same information to be decoded in different ways. This suggests that NEF is suitable for modeling expert performances, particularly in the context of games such as chess where the options and patterns are well-defined.